A Novel Radioimmune 99mTc-Labeled Tracer for Imaging Sphingosine 1-Phosphate Receptor 1 in Tumor Xenografts: An In Vitro and In Vivo Study - Ye, Min; Gai, Yongkang; Ji, Hao; Jiang, Yaqun; Qiao, Pengxin; Wang, Wenxia; Zhang, Yongxue; Xia, Xiaotian; Lan, Xiaoli (Frontiers in Immunology, 2021)
Sphingosine-1-phosphate (S1P) is a phospholipid that regulates pleiotropic biological activities and exerts extracellular functions by binding to five specific G-protein-coupled receptors, S1P receptors (S1PR) 1–5. When activated by S1P, S1PR promote the proliferation and invasion of tumor cells by inducing the formation of new blood vessels. We developed and assessed a new monoclonal antibody imaging probe 99mTc-HYNIC-S1P1mAb, to explore the feasibility of targeting the S1PR1 in vitro and in vivo. S1PR1mAb was prepared and followed by 99mTc labeling with succinimidyl 6-hydraziniumnicotinate hydrochloride. Cell uptake and blocking studies were performed to investigate the binding specificity of 99mTc-HYNIC-S1P1mAb in vitro. 99mTc-HYNIC-S1P1mAb was also tested in vivo in mice xenografted with SK-HEP-1 (high-expression of S1PR1) and MCF-7 (low-expression of S1PR1) using single-photon emission-computed tomography (SPECT). Ex vivo gamma counting of tissues from tumor-bearing mice was used to evaluate 99mTc-HYNIC-S1P1mAb biodistribution. The biodistribution study results showed significantly higher uptake in SK-HEP-1 tumors than in MCF-7 tumors (P < 0.001). Reduced uptake of 99mTc-HYNIC-S1P1mAb in SK-HEP-1 was observed in tumor-bearing nude mice pretreated with fingolimod, which binds competitively to the receptors, especially S1PR1. 99mTc-HYNIC-S1P1mAb can be synthesized and specifically targeted to S1PR1 in vitro and in vivo, allowing S1PR1 expression assessment with SPECT imaging.